2004
DOI: 10.4049/jimmunol.173.11.6949
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Soluble Form of Recombinant Extracellular TLR4 Domain with MD-2 Enables Lipopolysaccharide Binding and Attenuates TLR4-Mediated Signaling

Abstract: TLRs have been implicated in recognition of pathogen-associated molecular patterns. TLR4 is a signaling receptor for LPS, but requires MD-2 to respond efficiently to LPS. The purposes of this study were to examine the interactions of the extracellular TLR4 domain with MD-2 and LPS. We generated soluble forms of rTLR4 (sTLR4) and TLR2 (sTLR2) lacking the putative intracellular and transmembrane domains. sTLR4 consisted of Glu24-Lys631. MD-2 bound to sTLR4, but not to sTLR2 or soluble CD14. BIAcore analysis demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 35 publications
3
85
1
Order By: Relevance
“…43 sTLR4 protein (30 mg/ml), a molecule that may also function as an inhibitor of MBL, was pre-incubated with biotinylated MBL (10 mg/ml) at 37 uC for 30 min. HSA was used as a negative control.…”
Section: Analysis Of Mbl Binding To Thp-1 Cells By Fcmmentioning
confidence: 99%
“…43 sTLR4 protein (30 mg/ml), a molecule that may also function as an inhibitor of MBL, was pre-incubated with biotinylated MBL (10 mg/ml) at 37 uC for 30 min. HSA was used as a negative control.…”
Section: Analysis Of Mbl Binding To Thp-1 Cells By Fcmmentioning
confidence: 99%
“…sTLR4 and MD-2 cDNAs were described previously (37). sTLR4-His 6 was subcloned into pcDNA3.1(ϩ) (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…MD-2 binds to the extracellular TLR4 domain, and a complex of MD-2 and TLR4, but not TLR4 alone, can interact with LPS (37). POPG binds to MD-2 with high affinity.…”
Section: Phospholipid Antagonism Of Lps-induced Inflammationmentioning
confidence: 99%
“…sTLR4 consisting of the putative extracellular domain (Met 1 -Lys 631 ) and a 6ϫHis tag at the C-terminal end, sTLR2 consisting of the putative extracellular domain (Met 1 -Arg 587 ) and a 6ϫHis tag at the C-terminal end, and sMD-2 containing V5 tag and 6ϫHis tag were generated by the baculovirus-insect cell expression system, and the recombinant proteins were purified, as described previously (9,14). sTLR4 and sTLR2 start at Glu 24 and Glu 21 , respectively.…”
Section: Recombinant Proteinsmentioning
confidence: 99%
“…However, LPS beads coprecipitate sTLR4 and MD-2 when both proteins are coincubated, suggesting that the extracellular TLR4 domain-MD-2 complex, but not TLR4 alone, is capable of binding LPS. Addition of sTLR4 and sMD-2 attenuates LPS-elicited NF-B activation and IL-8 release in TLR4-expressing cells (9). One study has reported a 20-kDa naturally occurring soluble form of mouse TLR4 that is expressed by alternatively spliced TLR4 mRNA (10).…”
mentioning
confidence: 99%